Error Control Techniques For Video Transmission Over Wireless Channels - Chang, Yoong Choon (2008)
With the advancements in wireless communications technologies, wireless broadband service over 1Mbps is now gaining popularity in many countries due to its ubiquity and convenience. However, transmission of compressed video over wireless channels remains a challenging task due to the limited bandwidth and the error-prone nature of the wireless channels. It is thus the objective of this thesis is to improve the existing techniques on robust video transmission over wireless channels so that the received video quality at the receivers can be improved.